Pengembangan Modul Ajar Berbasis Pendekatan STEAM Berbantuan Google Sites Pada Mata Pelajaran Matematika di Kelas V Sekolah Dasar - Ermawasari Ermawasari; Ahmad Fauzan (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study was motivated by the need for innovative, interactive, and digitally integrated mathematics learning materials to improve the quality of instruction in elementary schools. The purpose of this study is to develop and evaluate the validity, practicality, and effectiveness of a STEAM-based mathematics teaching module supported by Google Sites for Grade V elementary school students. This research employed a Research and Development (R&D) method using the Plomp development model, which consists of three phases: preliminary research, prototyping stage, and assessment phase. The preliminary research phase involved needs analysis, curriculum analysis, analysis of students’ characteristics, and learning material analysis. The prototyping stage focused on designing and developing the STEAM-based teaching module supported by Google Sites, followed by self-evaluation and expert validation by material, media, and language experts. The assessment phase was conducted through limited trials, including practicality testing by teachers and students as well as effectiveness testing to determine the usefulness of the module in Grade V mathematics learning. The results showed that the STEAM-based teaching module supported by Google Sites achieved a very high level of validity, with validation scores of 95% for material, media, and language aspects. The module was also classified as very practical, with practicality scores of 98% in the small group trial and 97% in the field test. Furthermore, the effectiveness test yielded a score of 94%, indicating that the module is effective for use in Grade V elementary school mathematics learning.